Effects of Acute Probenecid Administration on Histopathological and Functional Outcomes after Spinal Cord Injury in Rats - Toru Asari; Sunao Tanaka; Damien D. Pearse; Juan Pablo de Rivero Vaccari; Toshitada Sawada; Yasuyuki Ishibashi; Robert W. Keane; W. Dalton Dietrich (Neurotrauma Reports)
Spinal cord injury (SCI) triggers an inflammatory response that is partially mediated by the inflammasome and the production of pro-inflammatory cytokines. We have previously shown that pannexin-1 is involved in the activation of the inflammasome, and that probenecid inhibits this caspase-1-mediated inflammatory process. In this study, we employed an in vivo model of contusive SCI to investigate the therapeutic effect of acute probenecid administration on histopathological and functional outcomes following SCI. Adult female Fischer rats (n = 46) underwent moderate thoracic SCI produced by dropping a 10 g weight from a height of 12.5 mm onto the exposed cord at T9, assigned three different groups, PBS administration group, and 1, 10, 100 mg/kg probenecid group, those were injected subcutaneously 15 min and 12 h after SCI. The sham group (n = 11) was the group that only had a laminectomy and did not have SCI. Histopathological analysis by Luxol Fast Blue/hematoxylin and eosin staining revealed that the penumbra volume was significantly reduced in the probenecid 100 mg/kg group compared with the PBS group. CatWalk gait analysis was performed at 7 weeks after SCI, which showed significant differences in coordination between the PBS and the probenecid 100 mg/kg-treated groups. Acute administration of probenecid after SCI resulted in the preservation of penumbra formation and coordination function in a thoracic SCI rat model. This report suggests that probenecid, an inhibitor of pannexin-1, has the potential to prevent secondary injury after SCI and improve outcomes following SCI.